Glycolytic Response to Inflammation Over Time: Role of Myeloid HIF-1alpha - Fitzpatrick, Susan F.; Gojkovic, Milos; Macias, David; Tegnebratt, Tetyana; Lu, Li; Samén, Erik; Rundqvist, Helene; Johnson, Randall S. (Frontiers in Physiology, 2018)
The in vivo response to lipopolysaccharide (LPS) occurs rapidly and has profound physiological and metabolic effects. The hypoxia inducible (HIF) transcription factor is an intrinsic and essential part of inflammation, and is induced by LPS. To determine the importance of the HIF response in regulating metabolism following an LPS response, glucose uptake was quantified in a time dependent manner in mice lacking HIF-1α in myeloid cells. We found that deletion of HIF-1α has an acute protective effect on LPS-induced hypoglycemia. Furthermore, reduced glucose uptake was observed in the heart and brown fat, in a time dependent manner, following loss of HIF-1α. To determine the physiological significance of these findings, cardiovascular, body temperature and blood pressure changes were subsequently quantified in real time using radiotelemetry measurements. These studies reveal the temporal aspects of HIF-1α as a regulator of the metabolic response to acute LPS-induced inflammation.